Can Anyone Climb? The Skills of a Non-specialized Toad and its Bearing on the Evolution of New Niches - Vassallo, Aldo Iván (2021)
Several studies of arboreal anuran species show morphological specializations for clinging onto narrow substrates. However, little is known about these capacities in non-specialized anurans, which is crucial to understand the initial phases of adaptation to a new niche. To assess the functional requirements related to the evolution of arboreality in anurans we analyzed climbing performance, and correlated anatomical traits, in the terrestrial toad Rhinellaarenarum, a species choose as a proxy for the ancestral condition regarding the evolution of this specialized niche. We studied the impact of a substrate of wooden rods with different diameters, arrangements, and slopes on locomotion, grasping, and climbing with a comparative framework. Animals were confronted with climbing tests, video recording their behaviors. Preserved specimens were dissected to assess limb myology, osteology, and tendons’ characteristics. Our results show that how terrestrial toad R.arenarum climbs is different from those displayed by specialized tree frogs. Animals flexed their fingers and toes, grasping the substrate displaying hookings and partial graspings. The palm was scarcely involved in the grip, as in specialized anurans. These actions were performed although flexor and extensor muscles of the digits are highly conserved and generalized. Further, we formally assess the evolutionary history of ecological and anatomical traits related to climbing among Rhinella species to improving the comprehension of the relation between morphofunctional patterns and behavioral climbing skills. Our experiments revealed that this terrestrial toad possesses unexpected climbing capacities, suggesting a way in which evolution of new niches could have developed in the evolution of anurans.